1998
DOI: 10.1046/j.1365-2168.1998.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma

Abstract: Hepatocellular carcinoma is commonly a problem of two diseases, the malignancy itself and cirrhosis. This renders treatment rarely curative, even when surgical resection can be applied in a technically successful sense. Liver transplantation could be a definitive treatment but this is plagued by limited donor resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
107
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 116 publications
3
107
0
1
Order By: Relevance
“…However, there is still some controversy regarding the indications for resection of HCC. HCC with diameter of less than 5 cm is regarded by some as the best candidate for resection because of increased risk of additional nodules or vascular invasion and consequently incomplete resection with larger HCCs [245,246]. However, it has been shown that patients with a large solitary HCC are suitable for successful resection and reasonable long-term survival results can be achieved [247,248].…”
Section: Liver Resectionmentioning
confidence: 99%
“…However, there is still some controversy regarding the indications for resection of HCC. HCC with diameter of less than 5 cm is regarded by some as the best candidate for resection because of increased risk of additional nodules or vascular invasion and consequently incomplete resection with larger HCCs [245,246]. However, it has been shown that patients with a large solitary HCC are suitable for successful resection and reasonable long-term survival results can be achieved [247,248].…”
Section: Liver Resectionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) accounts for more than 90% of all primary liver cancers and represents approximately 40% of all cancers in South-East Asia, Japan and Africa (Akriviadis et al, 1998). The majority of these HCC cases is often inoperable (Okuda et al, 1985) and the 5-year survival rate is limited to 25-50% after surgery (Colombo, 1992;Lai et al, 1995;Takenaka et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…HCC usually develops from chronic inflammatory liver diseases caused by viral infection or alcohol intake that induces cirrhosis [1], [2]. Another risk factor, exposure to chemical carcinogen such as aflatoxin B1 (AFB1), is also associated with tumorigenesis of the liver [3], [4].…”
Section: Introductionmentioning
confidence: 99%